Cardiovascular Rehabilitation: perspectives of patients and healthcare professionals on the implementation of multidisciplinary programs - Veloso, Ana; Rocha, Rita; Macedo, Gerly; Teixeira, Ana; Almeida, Vera (Scientific Letters, 2025)
Cardiovascular diseases are one of the main causes of global mortality, requiring integrated interventions to promote patient recovery. Cardiovascular rehabilitation is an essential approach that combines multidisciplinary care to improve quality of life and prevent recurrences. This study aims to explore the perceptions of the patients and health professionals about the implementation and effectiveness of the Unidade Local de Saúde do Alto Ave (ULSAA) Cardiovascular Rehabilitation Program (CVRP), identifying barriers and opportunities to improve its effectiveness. A qualitative study with a focus group methodology comprised eight patients and five health professionals. Data were analyzed based on Bardin’s content analysis methodology. Participants recognized the importance of the multidisciplinary approach, which promoted significant advances in physical and emotional recovery. However, challenges such as fragmentation of care, ineffective communication, and stigma associated with mental health were highlighted. Family involvement was considered essential, and adherence to the program varied due to factors such as personal motivation and limited understanding of the benefits. CVRP is a valuable intervention but faces some challenges. It is recommended to improve communication, expand psychological support, and invest in resources to strengthen cohesion between areas of activity.